The influence of romantic relationships on mental wellbeing for people who experience psychosis: A systematic review. (June 2021) - White, Rebecca; Haddock, Gillian; Campodonico, Carolina; Haarmans, Maria; Varese, Filippo
Abstract: Purpose: Whilst it is generally accepted that supportive relationships facilitate recovery from psychosis, much less is known about the role of romantic relationships in people with psychosis. This review aimed to synthesise quantitative literature regarding the impact of romantic relationships on the mental health and general wellbeing of people who experience psychosis. Method: A systematic review of electronic databases (PsychINFO, PubMed, Web of Science) was carried out using search terms relating to psychosis and romantic relationships. Papers were selected for inclusion by independent reviewers. Quality assessment was completed and a narrative synthesis produced. Results: Fifty-eight studies reporting the association between romantic relationships and psychotic symptoms, depression, posttraumatic stress disorder, suicidality, quality of life, satisfaction with life and self-esteem were included. Results were mixed but indicated having a romantic partner may be associated with reduced positive and negative symptoms of psychosis, but increased depressive symptoms. Tentative explanations for these findings, such as functioning prior to onset of psychosis, social support and relationship quality are explored. Conclusion: Findings highlight the importance of this often-overlooked area in clinical practice. Studies with robust design, which specifically aim to understand the relationship between romantic relationships and wellbeing for people who experience psychosis are needed. Highlights: Having a partner may be linked to fewer symptoms of psychosis. Romantic relationships may be particularly beneficial for young adults. Having a partner or having ever been in a relationship is linked to depression. The mechanisms responsible for improved outcomes require further scrutiny. More research is needed on intimate relationships, sexuality & mental wellbeing.